2018
DOI: 10.1128/aac.00005-17
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel Targets M1 Macrophages and Ameliorates Splenomegaly in Chronic Schistosomiasis

Abstract: Splenomegaly is a common feature of many infectious diseases, including schistosomiasis japonica. However, the immunopathogenesis and the treatment of splenomegaly due to schistosomiasis have been largely neglected. Praziquantel (PZQ), a classical schistosomicide, has been demonstrated by us and others to have antifibrotic and anti-inflammatory activities against schistosomiasis. In this study, we investigated the effect of PZQ on alleviating the splenomegaly caused by infection in mice. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
0
18
1
Order By: Relevance
“…Similarly, all of these inflammasome-related markers decreased in expression following Sch B treatment; except for IL-18, which showed an increased expression. One study has confirmed the increase of NLRP3 in the spleen of S. japonicum-infected mice [40], but none has shown the effect of Schistosoma infection on the downstream effector proteins. Hence, we conceivably hypothesized that there might be other pathways involved in the change of IL-18.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, all of these inflammasome-related markers decreased in expression following Sch B treatment; except for IL-18, which showed an increased expression. One study has confirmed the increase of NLRP3 in the spleen of S. japonicum-infected mice [40], but none has shown the effect of Schistosoma infection on the downstream effector proteins. Hence, we conceivably hypothesized that there might be other pathways involved in the change of IL-18.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Inflammasomes are presented in various immune cells [38] and have been shown to express in macrophages during schistosomiasis [39,40]. To further clarify how Sch B affects G, I, and K), the number and the corresponding areas of each circled area were potted directly on the graph.…”
Section: Schisandrin B Reduces Macrophages Proliferation and Their Activation Of The Inflammasomementioning
confidence: 99%
“…It is reported that the high level of miR-21 induced by Opisthorchis viverrini-infection in patients was reduced significantly by PZQ treatment (44). Moreover, PZQ treatment significantly reduced spleen pathological damage induced by chronic infection of schistosomiasis in mice (18). A recent study has shown that PZQ promotes human Type 1 regulatory T cell differentiation, suggesting that PZQ may also have immunomodulatory functions in parasite-unrelated human inflammatory diseases (45).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have revealed that long-term PZQ treatment had anti-inflammatory effects and considerably improved S. japonicum-induced splenomegaly and liver fibrosis (16,17). Moreover, PZQ alleviated the pathological damage of the spleen in mice with chronic S. japonicum infection by regulating macrophage polarization and attenuating the phagocytic activity of M1 macrophages (18). However, little is known about the underlying mechanisms of anti-inflammatory effects of PZQ.…”
Section: Introductionmentioning
confidence: 99%
“…Praziquantel (PZQ) is the primary drug for treating schistosomiasis. Although PZQ has been shown to aid in ameliorating liver fibrosis via multiple mechanisms in murine models of schistosomiasis [16, 17], PZQ cannot completely reverse the progression of chronic liver fibrosis, and the excessive reliance on this drug to treat schistosomiasis has raised concerns about drug resistance [18]. Therefore, effective therapeutic methods for treating schistosomiasis-associated hepatic fibrosis are urgently needed [19].…”
Section: Introductionmentioning
confidence: 99%